Answer:
Step-by-step explanation:
![\boxed{\underline{\text{ORDER OF OPERATIONS:}}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cunderline%7B%5Ctext%7BORDER%20OF%20OPERATIONS%3A%7D%7D%7D)
Use the order of operations.
Note: PEMDAS or BODMAS stands for:
<u>PEMDAS</u>
- <u>Parentheses</u>
- <u>Exponents</u>
- <u>Multiply</u>
- <u>Divide</u>
- <u>Add</u>
- <u>Subtract</u>
<u>BODMAS</u>
- <u>Brackets</u>
- <u>Order</u>
- <u>Divide</u>
- <u>Add</u>
- <u>Subtract</u>
<u>First, do parentheses.</u>
3+6*(5+4)÷3-7
(5+4)=9
![\Longrightarrow: \sf{3+6* 9\div 3-7}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Csf%7B3%2B6%2A%209%5Cdiv%203-7%7D)
<u>Do multiply and divide.</u>
6*9=54
54/3=18
<u>Then, rewrite the problem down.</u>
![\Longrightarrow: \sf{3+18-7}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Csf%7B3%2B18-7%7D)
<u>Add.</u>
![\sf{3+18=21}](https://tex.z-dn.net/?f=%5Csf%7B3%2B18%3D21%7D)
![\sf{21-7=\boxed{\sf{14}}](https://tex.z-dn.net/?f=%5Csf%7B21-7%3D%5Cboxed%7B%5Csf%7B14%7D%7D)
![\Longrightarrow: \boxed{\sf{14}}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Cboxed%7B%5Csf%7B14%7D%7D)
- <u>Therefore, the correct answer is "C. 14".</u>
I hope this helps, let me know if you have any questions.
<u>Answer</u>:
equation: y = x/2
<u>Explanation</u>:
let the points be (-6, -3) , ( 0, 0)
slope: ![\frac{y2-y1}{x2-x1}](https://tex.z-dn.net/?f=%5Cfrac%7By2-y1%7D%7Bx2-x1%7D)
: ![\frac{0--3}{0--6}](https://tex.z-dn.net/?f=%5Cfrac%7B0--3%7D%7B0--6%7D)
: ![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
Equation using:
y - y1 = m ( x - x1 )
y - - 3 = 1/2( x - - 6 )
y + 3 = x/2 + 3
= ![\frac{x}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D)
Answer: 33
Step-by-step explanation:
Input the numbers into the variables.
7(2) + 3 + 16
14 + 3 + 16
17 + 16
33
Answer: No, it is not a solution
==========================================================
Explanation:
The point (3,-4) means that x = 3 and y = -4 pair up together
Let's plug these x,y values into each equation
Starting with the first equation, we get,
y = 4x-16
-4 = 4(3)-16 ... x replaced with 3; y replaced with -4
-4 = 12-16
-4 = -4 .... this is a true statement
Repeat for the second equation
y = 2x-6
-4 = 2(3)-6
-4 = 6-6
-4 = 0 ... this is false
Since we get a false statement, this means (3,-4) is not on the line y = 2x-6, which means that overall (3,-4) is not a solution to the system of equations. The point (3,-4) must make both equations true for it to be a solution.
Answer:
temporary life insurance and permanent life insurance
Step-by-step explanation: